THE CONFLICT BETWEEN VISION AND TOUCH: ON VISUAL CAPTURE - KEZUKA, EMIKO (Shinrigaku kenkyū, 1979)
This paper aims to examine the limitation of visual dominance under a situation of conflict between the visual and tactile shape of an object. The subjects were presented with an object of which shape was made to appear different visually from its tactile shape by optical distortion. To change the degree of conflict, three reducing lenses of differing powers were used. After simultaneously grasping and viewing the standard object, the subjects were asked to choose a comparison object in accordance with their impression of the shape of the standard. The results showed that the degree of visual capture was limited. Using a lens that reduced the apparent visual image approximately 1/8, most subjects were aware of the conflict between the visual and tactile impressions.